The Influence of Mental Health, Study Habits and Achievement Motivation on Students’ Success at MTsN 4 Surabaya - Ida Fitriyah, Eting; Darmawan , Didit (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2024)
This study aims to investigate the effect of mental health and study habits on student achievement at State Tsanawiyah Madrasah 4 Surabaya City. The study population included all State Tsanawiyah Madrasah 4 Surabaya City students, totalling 704 students. The research sample was randomly drawn from students in Class VII, totalling 277 students. Data analysis was conducted using the statistical method of regression analysis to identify the extent of the influence of the three independent variables on the dependent variable. The results showed that students' mental health has a significant influence on learning achievement. Students with good mental health tend to be able to cope with pressure and stress, allowing them to focus and concentrate better during the learning process. Students' study habits were also shown to play an important role in shaping learning achievement. Regular and structured study habits help students to effectively manage time and study tasks, creating the basis for optimal achievement. In conclusion, mental health and study habits play a crucial role in shaping student achievement.